Effects of Visual Working Memory on Individual Differences in Echolocation Performance in Sighted Participants. (August 2019) - Maezawa, Tomoki; Kawahara, Jun I.
Echolocation performance differs widely among individuals. This study examined a possible factor that may explain this variation, namely, visual working memory, which is a subcomponent of spatial working memory. Sighted participants performed an object-detection task consisting of initial testing on 2 separate days (up to 8 days apart) with follow-up testing on a third day (up to 1 month after the second day of testing) while manipulating the target distance from 20 to 50 cm. Participants performed two types of visual spatial working memory tasks, one of which required them to memorize color–location combinations and the other, an imaginary pathway. The participants' performance on the object-detection task generally improved in the first 2 days, but there were substantial individual differences in detection ability. A positive correlation was observed between performance on these tasks and visual working memory capacity, except on the second day, after detection ability had improved. These findings suggest that factors contributing to echolocation skill are related to nonauditory factors in a sighted group.